Swedish crime fiction : Novel, film, television - Peacock, Steven, 1974- (Book collections on Project MUSE., 2014)
Swedish crime fiction became an international phenomenon in the first decade of the 21st century, starting first with novels but then percolating through Swedish-language television serials and films and onto English-language BBC productions and Hollywood remakes. This book looks at the rich history of 'Scandinavian noir', examines the appeal of this particular genre and attempts to reveal why it is distinct from the plethora of other crime fictions.